2016
DOI: 10.3892/br.2016.583
|View full text |Cite
|
Sign up to set email alerts
|

4-Nitroquinoline-1-oxide effects human lung adenocarcinoma A549 cells by regulating the expression of POLD4

Abstract: Abstract. The aim of the present study was to explore the expression of POLD4 in human lung adenocarcinoma A549 cells under 4-nitroquinoline-1-oxide (4NQO) stimulation to investigate the role of POLD4 in smoking-induced lung cancer. The lung cancer A549 cell line was treated with 4NQO, with or without MG132 (an inhibitor of proteasome activity), and subsequently the POLD4 level was determined by western blot analysis. Secondly, the cell sensitivity to 4NQO and Taxol was determined when the POLD4 expression lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…As reported, POLD4 functioned in cell proliferation and maintenance of genomic stability of human cells [34]. Low expression of POLD4 was reported to weaken the DNA repair systems including nucleotide excision repair and increase the risk of lung cancer formation [35]. Huang et al also reported that POLD4 was low expressed in human lung cancer and was associated with poor prognosis; reduction of POLD4 in lung cancer cells resulted in cell cycle delay, checkpoint activation, and an elevated frequency of chromosomal gap/break formation [36].…”
Section: Discussionmentioning
confidence: 78%
“…As reported, POLD4 functioned in cell proliferation and maintenance of genomic stability of human cells [34]. Low expression of POLD4 was reported to weaken the DNA repair systems including nucleotide excision repair and increase the risk of lung cancer formation [35]. Huang et al also reported that POLD4 was low expressed in human lung cancer and was associated with poor prognosis; reduction of POLD4 in lung cancer cells resulted in cell cycle delay, checkpoint activation, and an elevated frequency of chromosomal gap/break formation [36].…”
Section: Discussionmentioning
confidence: 78%
“…Huang et al 104 have identified that circAKT3 promotes DNA damage repair via miR-198/PIK3R1. Hsa_circ_0026359 sponges miR-1200 and upregulates POLD4 105 , and low expression of hsa_circ_0026359 has been reported to weaken DNA repair systems 106 . In addition, circPRMT5 overexpression in lung cancer enhances cisplatin resistance by upregulating REV3 L, which encodes the catalytic subunit of DNA polymerase ζ and is responsible for translesional replication 107 .…”
Section: Circrnas Promoting Dna Repair In Chemoresistancementioning
confidence: 99%
“…Loss of POLD4 results in a defect in HR and sensitization to PARP inhibitors, indicating that an indispensable component of Polδ is necessary for functional HR [ 14 ]. POLD4 has been observed in the development and progression of multiple cancers, including hepatocellular carcinoma [ 15 ], lung cancer[ 16 , 17 ], and cisplatin resistance in gastric cancer [ 18 ]. In GBMs, POLD4 is associated with cancer patient resistance to radiotherapy and tumor recurrence [ 19 ].…”
Section: Introductionmentioning
confidence: 99%